Carbonic anhydrase 2‐like in the giant clam, Tridacna squamosa: characterization, localization, response to light, and possible role in the transport of inorganic carbon from the host to its symbionts - Yuen K. Ip; Clarissa Z. Y. Koh; Kum C. Hiong; Celine Y. L. Choo; Mel V. Boo; Wai P. Wong; Mei L. Neo; Shit F. Chew (Physiological Reports, 2017)
Abstract The fluted giant clam, Tridacna squamosa, lives in symbiosis with zooxanthellae which reside extracellularly inside a tubular system. Zooxanthellae fix inorganic carbon (Ci) during insolation and donate photosynthate to the host. Carbonic anhydrases catalyze the interconversion of CO2 and HCO3−, of which carbonic anhydrase 2 (CA2) is the most ubiquitous and involved in many biological processes. This study aimed to clone a CA2 homolog (CA2‐like) from the fleshy and colorful outer mantle as well as the thin and whitish inner mantle of T. squamosa, to determine its cellular and subcellular localization, and to examine the effects of light exposure on its gene and protein expression levels. The cDNA coding sequence of CA2‐like from T. squamosa comprised 789 bp, encoding 263 amino acids with an estimated molecular mass of 29.6 kDa. A phenogramic analysis of the deduced CA2‐like sequence denoted an animal origin. CA2‐like was not detectable in the shell‐facing epithelium of the inner mantle adjacent to the extrapallial fluid. Hence, CA2‐like is unlikely to participate directly in light‐enhanced calcification. By contrast, the outer mantle, which contains the highest density of tertiary tubules and zooxanthellae, displayed high level of CA2‐like expression, and CA2‐like was localized to the tubule epithelial cells. More importantly, exposure to light induced significant increases in the protein abundance of CA2‐like in the outer mantle. Hence, CA2‐like could probably take part in the increased supply of inorganic carbon (Ci) from the host clam to the symbiotic zooxanthellae when the latter conduct photosynthesis to fix Ci during light exposure.